Glyphosate Application and Potential Eleusine Indica Resistance in Oil Palm Plantations - Muin, Abdul; Wirianata, Herry; Nugraha, Teguh (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Eleusine indica is a grass weed in oil palm plantations, especially during the period of immature crops. The application of glyphosate for weed control shows diverse effectiveness. This study aims to determine the age of susceptible weeds in increasing the effectiveness of glyphosate in controlling E. indica. The study tested the application of glyphosate with three levels (486, 729, and 972 g/ha) at three different weed ages (3, 6, and 9 weeks). E. indica was taken from oil palm plantations that were previously glyphosate-depleted, then sprayed with glyphosate according to the dose studied. Each treatment combination is represented by five pots containing five individual weeds. The results showed that the application of glyphosate aged three and six weeks of higher effectiveness controlled E. indica for doses of 486 and 729 g/ha) than a nine-week application for all doses tested. Regrowth of weeds is found mainly the application of glyphosate at the age of a month of weeks. The development of E. indica's resistance to glyphosate needs attention in oil palm plantations.